Water Quality Assessment of Brahma Sarovar: A Sacred Lake at Kurukshetra (India) - Deswal, Surinder; Dogra, Sachin Kumar (Ecological Questions, 2023)
Brahama Sarovar, in Kurukshetra city (India), is an ancient sacred lake where devotees perform various religious activities/offerings on daily basis, and on special occasions of solar and lunar eclipses, millions of pilgrims all over the country have mass bathing (holy-dip) for internal and external purity. Along with religious importance, this artificial lake also acts as a sacred grove/wetland that serves as an important wintering and stopover site for migratory birds from the Palearctic region. The study was carried out with the objective to analyze the improvement in water quality status after the provision of a closed conduit for the supply of fresh water to the lake and additional measures required for public health safety. For this, the water quality of this sacred lake has been spatially analyzed and compared with Indian standards prescribed for ‘Designated Best Use Class-B: Outdoor Bathing (Organised)’ in the present study. Though the parameters – pH (7.94 within the limits of 6.5-8.5), turbidity (3.63 < 5 NTU), TDS (222.33 < 500 mg/L), TSS (100.25 mg/L) and MPN (239.25 ≤ 500 per 100 ml) were observed to be within the permissible limits, but DO (4.7 ≤ 5.0 mg/L) and BOD (3.54 ≥ 3.0 mg/L) of the lake water were found beyond the permissible limits. Thus, making the lake water unfit for human use for bathing. The comparison with the previous two studies revealed that the lake’s water quality has improved in the last couple of years through the provision of a closed conduit, in place of an open channel, for the supply of fresh canal water to the lake. A couple of additional measures have also been suggested to maintain the water quality standards in the lake so as to protect the human health of the devotees and pilgrims.